PENGARUH PEMBERIAN INFUSA HERBA CIPLUKAN (Physalis angulata L) TERHADAP KADAR KOLESTEROL TOTAL PADA TIKUS JANTAN WISTAR YANG DIBERI DIET LEMAK TINGGI - Sari Fitriani (Khazanah: Jurnal Mahasiswa, 2016)
Cholesterol has been discussed topic in community. Assosiated with its complications which increase the risk of cardiovascular disease, treatment and prevention efforts even more seriously. One of them is, by using ciplukan plant (Physalis angulata L) that is believed may decrease cholesterol level in blood. This research aimed to know the effect infusa herbs ciplukan on white wistar male rats given high fat diet. We use fourty two white wistar male rats were divided into 7 groups (N=6). The normal group was just given BR-II diet. The negative control group were given diet high fat from the first day to 49th without giving fenofibrat or infusa. The positive control group were given a diet high fat from the first day to 49th and given fenofibrat start until 36th day to 49th day. Groups 4, 5, 6, and 7 is that the treatment group were given a high fat diet from the first day to 49th and given infusa herb ciplukan with each 2,5%; 5%; 10%; and 20% b/v start until 36th day to 49th day. Cholesterol level measurements using methods enzymatic colorimetric test. Data obtained on the day to 14, 28, 35, 42, and 49 analyzed by using one-way ANOVA test with a 95% rate trust. Treatment with infusa herb ciplukan 2,5%; 5%; 10%; and20% in 36 days to up to 49 th days can decrease the level of total cholesterol 41,78%, 53,84%, 68,38%, and 79,77%. Results of this research show that infusa herb ciplukan have any significant effect on the decrease of total blood cholesterol level compared with the negative control (p <0.5).Keywords: cholesterol, hiperlipidemia, Physalis angulata L